Product diversification, relative specialisation and economic development: Import-export analysis - Aleksandra Parteka; Massimo Tamberi (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
This paper contributes to trade diversification literature by comparing changes in relative (i.e. assessed in comparison with world patterns) heterogeneity of import and export structures in the process of economic development. In particular, by focusing on the diversification of imports, we add a missing piece to already analysed export trends. We use highly disaggregated trade statistics (4963 product lines) for 163 countries (1988-2010) and find that, despite differences in levels (imports being typically more diversified than exports, particularly at lower stages of economic development), they follow a similar path of evolution in the development process. Progressing relative diversification (despecialisation) of both import and export structures accompanies economic growth, while re-specialisation is plausible only in case of few specific countries (very rich, small ones, abundant in oil/petrol). We also show that even though while diversifying countries increase the degree of import-export similarity in terms of product categories, imported and exported goods differ in terms of within-product characteristics.
Keywords: F14; O11; 330; diversification; specialisation; trade; economic development